Motion estimation from satellite image sequences: validation - Huot, E.; Herlin, I.; Mercier, N.; Korotaev, G.; Plotnikov, E. (Екологічна безпека прибережної та шельфової зон та комплексне використання ресурсів шельфу, 2011)
This report concerns the validation of surface velocity estimated from satellite images. The estimation is obtained with a dynamic model based on shallow-water equations. We first compare the stationary assumption to the shallow-water heuristics to justify our choice. Second, we quantify the quality of the estimation by measuring the misfit between the model output and the altimetry measures. Experiments are achieved on Sea Surface Temperature data acquired by the NOAA/AVHRR satellites over the Black Sea. The altimetry measures are obtained by two radar sensors: Envisat and GFO. The good adequacy between the shallow-water output and the altimetry data validates our motion estimation approach.